The unstable pacing thresholds of the leadless transcatheter pacemaker affected by body positions in subacute phase after implant. Issue 1 (27th December 2018) - Yoh, Masue; Takagi, Masahiko; Takahashi, Hiroki; Yoshio, Takuro; Shiojima, Ichiro
Abstract: Background: If the threshold at implant of leadless transcatheter pacemakers (LTPs) is less than 2.0 V, pacing thresholds reportedly decrease significantly by 1 month and maintain an optimal value of less than 1.0 V by 6 months. Case summary: We report a case series of two patients with unstable pacing thresholds of the LTPs in the subacute phase after implant. The first patient (77-year-old man) was implanted an LTP for sick sinus syndrome. At that time of implant, the pacing threshold was 0.9 V at 0.24 ms. At 1 week and 1 month later, the threshold had increased to more than 2.0 V at 0.24 ms. We investigated the trend data for the week and found variations in the threshold. The second patient (81-year-old man) was implanted an LTP for bradycardia and atrial fibrillation. The pacing threshold at implantation was 0.63 V at 0.24 ms. One week later, the threshold had increased in supine position and decreased in sitting position. The trend data for the week were fluctuating greatly. Discussion: The pacing threshold may increase to more than 2.0 V with significant fluctuation on assessment at 1 week and 1 month after implantation in association with changes in body position, even though we confirmed a stable threshold at implant. If an increased threshold is observed, it is necessary to check the trend data and threshold in each body position.